The Eurozone Crisis: A Constitutional Analysis - Sting, Anna (Utrecht Journal of International and European Law, 2015)
“Every power comes through crisis” has long been a motif of European integration. The financial and sovereign debt crises, which have shaken the European Union (EU) in recent years, are at first glance no different. Treaty reforms, intergovernmental treaties such as the Fiscal Compact and the Treaty Establishing a European Stability Mechanism (ESM Treaty) have significantly altered the constitutional landscape of the EU and its Member States. The crisis has also inspired many European legal scholars to critically analyse the EU’s system of economic governance, as have other events throughout the history of the European Union, from the Empty Chair Crisis to the referenda in the aftermath of the Treaty of Maastricht and the failure of the Constitution for the European Union. What does seem to be different is the way in which scholars approach the issue of the Eurozone crisis. Instead of a purely legal perspective on economic governance, European legal scholars have realised that in order to understand and analyse the euro crisis, interdisciplinarity is the word of the moment.